Large spill of mining wastes in Portelo stream (Douro Basin NE Portugal) Impacts on ecosystem integrity - Teixeira, Amílcar (2014)
Streams located at Montesinho Natural Park (NE Portugal) have, generally, high biodiversity and an excellent ecological status. However, in this area there arc several abandoned mine sites. As a consequence of intense precipitation during December 2009, several millions of cubic meters of wastes were spilled into Portelo stream, a tributary of Rio Sabor (Douro basin).